Social skill assessment for transvestives through the implementation of social problem solving method - Aman Aman (Universitas Negeri Yogyakarta, 2016)
This study is aimed to know: 1) how the steps of assessment instrumen building of social skill for transvestives through social problem solving method are, 2) instrument appropriateness of transvestives’ social skill assessment is. This study uses Research and Development method consisting of four stages, which are: (1) introduction stage, (2) design organizing stage of social skill assessment instrument for transvestives as the development of initial product form, (3) trial, evaluation and revision stage, and (4) implementation stage. The numbers of transvestives who become the sample in each trial in 2015 is 5 transvestives selected using purposive sampling. The data collection technique uses FGD, questionaire, observation, and documentation techniques. The data validation uses expert validation, while the accuracy of qualitative data uses source triangulation technique, theory and method. The quantitative data analysis is conducted using descriptive and qualitative data analytic technique with interactive model. Based on the research result, it is concluded as follow: 1) the steps of instrument building on social skill assessment for transvestives through the implementation of social problem solving model are through : a) introductory study to construct theoretical framework, b) plan and organize instrument through FGD and expert validation, c) limited trial or individual test, evaluation and revision of instrument. The guidelines of expert validation result instrument indicates average score as 3.89 which means that the guideline is good or appropriate to test. Also, based on the transvestivesassessment in individual trial indicates good result with average score of 3.69. Meanwhile, the character education model of Social Problem Solving (SPS) for transvestives as the effort to develop their social skill in Special Region of Yogyakarta indicates good result with average score of 3.80.